Large deviations for the 3D stochastic Navier-Stokes-Voight equations. Issue 6 (26th April 2018) - Liu, Hui; Sun, Chengfeng
Abstract: In this paper, using the weak convergence method, a large deviation principle for 3D stochastic Navier–Stokes–Voight equations is proved.